Effect of beta-alanine with and without sodium bicarbonate on 2,000-m rowing performance - Hobson, R. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
To examine the effect of beta-alanine only and beta-alanine with sodium bicarbonate supplementation on 2,000-m rowing performance. Methods: Twenty well-trained rowers (age 23 ± 4 y; height 1.85 ± 0.08 m; body mass 82.5 ± 8.9 kg) were assigned to either a placebo or beta-alanine (6.4 g·d-1 for 4 weeks) group. A 2,000-m rowing time trial (TT) was performed before supplementation (Baseline) and after 28 and 30 days of supplementation. The post supplementation trials involved supplementation with either maltodextrin or sodium bicarbonate in a double-blind, crossover design, creating four study conditions (placebo with maltodextrin; placebo with sodium bicarbonate; beta-alanine with maltodextrin; beta-alanine with sodium bicarbonate). Blood lactate, pH, bicarbonate, and base excess were measured pre-TT, immediately post-TT and at TT+5 min. Performance data were analyzed using magnitude based inferences. Results: Beta-alanine supplementation was very likely to be beneficial to 2,000-m rowing performance (6.4 ± 8.1 s effect compared with placebo), with the effect of sodium bicarbonate having a likely benefit (3.2 ± 8.8 s). There was a small (1.1 ± 5.6 s) but possibly beneficial additional effect when combining chronic beta-alanine supplementation with acute sodium bicarbonate supplementation compared with chronic beta-alanine supplementation alone. Sodium bicarbonate ingestion led to increases in plasma pH, base excess, bicarbonate, and lactate concentrations. Conclusions: Both chronic beta-alanine and acute sodium bicarbonate supplementation alone had positive effects on 2,000-m rowing performance. The addition of acute sodium bicarbonate to chronic beta-alanine supplementation may further enhance rowing performance.